Concept and functions of building a private network (VPN) (Моделювання, керування та інформаційні технології, 2021)
As companies and organizations began to actively use computers in various areas of their work,  these computers needed to be integrated into a common network for fast data transfer and efficient interaction. However, this connection must have been reliable and secure.